2010
DOI: 10.1161/atvbaha.109.194902
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Modulates HIF-1α, VEGF, IL-8, and Foam Cell Formation in a Human Model of Hypoxic Foam Cells

Abstract: Objective-Foam cell (FC) formation by oxidized low-density lipoprotein (oxLDL) accumulation in macrophages is crucial for development of atherosclerosis. Hypoxia has been demonstrated in atherosclerosis and hypoxia-inducible factor-1 (HIF-1) has been shown to promote intraplaque angiogenesis and FC development. M acrophage foam cell formation is an important process in atherosclerotic plaque development. 1 Atherosclerosis is initiated by dysfunction of endothelial cells at lesionprone sites in the walls of art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 38 publications
0
60
0
1
Order By: Relevance
“…Recently, A 3 AR stimulating degranulation has been demonstrated also in LAD2 bone marrow-derived human mast cells (Leung et al, 2014). Human eosinophils were the first cells in which native hA 3 AR was detected by using radioligand binding (Kohno et al, 1996a;Morschl et al, 2008), and this was then followed by human neutrophils (Bouma et al, 1997;Gessi et al, 2002;Chen et al, 2006;van der Hoeven et al, 2008;Corriden et al, 2013;Mulloy et al, 2013), monocytes (Broussas et al, 1999(Broussas et al, , 2002Thiele et al, 2004), macrophages (McWhinney et al, 1996;Szabo et al, 1998;Gessi et al, 2010a), foam cells (Gessi et al, 2010a), dendritic cells (Panther et al, 2001;Fossetta et al, 2003;Dickenson et al, 2003;Hofer et al, 2003), lymphocytes (Gessi et al, 2004b;Varani et al, 2009Varani et al, , 2010b, splenocytes, bone marrow cells, lymphonodes , and synoviocytes (Varani et al, 2008(Varani et al, , 2010cStamp et al, 2012). Human chondrocytes and osteoblasts, two key cell types in the skeletal system, were recently found to express A 3 AR .…”
Section: Distribution Of the A 3 Adenosine Receptormentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, A 3 AR stimulating degranulation has been demonstrated also in LAD2 bone marrow-derived human mast cells (Leung et al, 2014). Human eosinophils were the first cells in which native hA 3 AR was detected by using radioligand binding (Kohno et al, 1996a;Morschl et al, 2008), and this was then followed by human neutrophils (Bouma et al, 1997;Gessi et al, 2002;Chen et al, 2006;van der Hoeven et al, 2008;Corriden et al, 2013;Mulloy et al, 2013), monocytes (Broussas et al, 1999(Broussas et al, , 2002Thiele et al, 2004), macrophages (McWhinney et al, 1996;Szabo et al, 1998;Gessi et al, 2010a), foam cells (Gessi et al, 2010a), dendritic cells (Panther et al, 2001;Fossetta et al, 2003;Dickenson et al, 2003;Hofer et al, 2003), lymphocytes (Gessi et al, 2004b;Varani et al, 2009Varani et al, , 2010b, splenocytes, bone marrow cells, lymphonodes , and synoviocytes (Varani et al, 2008(Varani et al, , 2010cStamp et al, 2012). Human chondrocytes and osteoblasts, two key cell types in the skeletal system, were recently found to express A 3 AR .…”
Section: Distribution Of the A 3 Adenosine Receptormentioning
confidence: 99%
“…However, although a genetic deficiency in the A 3 AR subtype has been demonstrated as significantly reducing the proliferative potential of aortas in organ culture, it does not attenuate the development of atherosclerotic lesions in response to a high-fat diet or vascular injury in vivo (Jones et al, 2004). On the other hand, it has been shown that, in hypoxic foam cells, adenosine stimulates HIF-1a accumulation, vascular endothelial growth factor secretion, and foam cell formation, suggesting the potential use of A 3 AR antagonists in blocking major steps in atherosclerotic plaque development (Gessi et al, 2010a).…”
Section: B Cardiovascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivation of A 2A receptors protects apolipoprotein E-deficient mice from atherosclerosis (Wang et al, 2009a). Adenosine modulates HIF-1a, VEGF, IL-8, and foam cell formation in a human model of hypoxic foam cells (Gessi et al, 2010). The authors claim that A 2B and A 3 antagonists may be able to block steps in the atherosclerotic plaque development.…”
Section: B Atherosclerosis and Coronary Artery Diseasementioning
confidence: 99%
“…Although adenosine signaling through hypoxia-inducible factor-1 (HIF-1), a key transcription factor responsible for the tissue adaptation to ischemia, has been studied in detail (Merighi et al, 2005(Merighi et al, , 2006De Ponti et al, 2007;Ramanathan et al, 2007Ramanathan et al, , 2009Alchera et al, 2008;Gessi et al, 2010), the role of other transcription factors in the adenosine-dependent VEGF production is not known. In addition to HIF-1, several transcription factor-binding sites for activator protein-1 (AP-1), AP-2, early growth response-1, specificity protein 1/3, and signal transducer and activator of transcription 3 have been identified within a 1.2 kb region of both mouse and human VEGF promoters (for review, see Pages and Pouyssegur, 2005).…”
Section: Introductionmentioning
confidence: 99%